Bilateral political tension and the signaling role of patenting in a host country - Zhou, Nan; Li, Jiatao; Wang, Jue (Journal of International Business Studies, 2024)
Abstract The current increasing volatility in international politics makes it more important to understand how multinational enterprises respond to political tension between host and home countries. This paper explains the impact of macro-level bilateral political tension on micro-level strategy of multinationals in the host country. We developed the idea that patenting may be used to signal a firm’s commitment and contribution to the host country’s economy and development. Data on 437 large multinationals and interviews with senior managers of 20 foreign subsidiaries in China show that patenting local innovation does indeed help an investing firm signal its usefulness to the host country government. It can thus serve as a response to bilateral political tension. The relationship between political tension and local patenting also depends on the relative trade dependence of the home and host countries and on the investing firm’s technology level and its stake in China. The greater the dependence of an MNE and its home country government on the host country, the more likely patenting of local innovations would increase in times of bilateral political tension.